План капитального строительства - Лапидус Михаил Хловенович (Техпромфинплан предприятия, 1972)
Экземпляры: КХ (20220125) / Инвентарный номер: 0210862 / Сис.шифр: 338 / Авт.знак: Л 24 / ГРНТИ: 06 / ББК: 65